Introduction to veterinary pathology - Cheville, Norman F. (Iowa State University Press, 2000)
This CD is constructed for the beginning student in veterinary pathology, to introduce new scientific information on mechanisms of general tissue injury into the language of medicine. The basic concepts of pathology are integrated into clinical medicine. Chapters on cellular degeneration and necrosis, inflammation, thrombosis, hemodynamic disorders, and neoplasia have been reconstructed to include the latest in new scientific information and color illustrations of gross pathology